FIBEROPTIC ENDOSCOPIC EVALUATION OF SWALLOWING: EXPERIENCE AT THE NATIONAL REHABILITATION HOSPITAL (2019 - 2025) - Linh, Nguyen Manh (Journal of Health and Aging, 2025)
Dysphagia is increasingly recognized due to higher survival rates after central nervous system injuries, head and neck cancer treatment, and in some cases in healthy elderly individuals. It leads to severe consequences including prolonged hospitalization, delayed recovery, recurrent pneumonia, and even mortality. Bedside clinical tests alone are insufficient for diagnosis. Fiberoptic Endoscopic Evaluation of Swallowing (FEES) is one of the gold standards in dysphagia assessment, proven to be safe, effective, and feasible worldwide. However, FEES has not been widely adopted in Vietnam. This paper reports the implementation and clinical experience of FEES at the National Rehabilitation Hospital between 2019 and 2025. Literature review and clinical experience were combined. More than 700 FEES procedures were performed between April 2019 and July 2025. FEES allowed direct visualization of swallowing physiology, identification of penetration/aspiration, and guided compensatory strategies. No serious complications were reported, apart from mild discomfort. FEES is an effective and safe diagnostic tool for dysphagia, supporting individualized management strategies and should be expanded in Vietnam.
Keywords: FEES; dysphagia; fiberoptic endoscopic evaluation of swallowing